The role of environmental policy in promoting green transportation technologies - Suthakavatin Siphimvadee; Shatila Khodor; Aydinyan Karine; Santy Raeni Dwi (BIO Web of Conferences)
This study explores the role of environmental policy in promoting the adoption of green transportation technologies, focusing on the effects of financial incentives, regulatory frameworks, and public investment in infrastructure across key Asian urban centres. The research highlights how technological innovation acts as a crucial mediator between policy measures and the adoption of sustainable transportation options such as electric vehicles (EVs) and hydrogen-powered vehicles. Using Structural Equation Modelling (SEM), the study examines the relationships between these factors, demonstrating that higher levels of financial incentives, supportive regulations, and strategic public investment lead to significant advancements in technological innovation, which in turn drives the adoption of green transportation technologies. The findings contribute to the broader understanding of sustainable urban mobility solutions and offer important insights for policymakers and industry stakeholders in regions experiencing rapid urbanization. The study also discusses the dual role of these policy drivers, both in directly influencing adoption and in fostering technological advancement.